Response to drought among farmers and herders in southern Kajiado District, Kenya - Campbell, David (Human Ecology, 1984)
Keywords: openalex:import

Coping with drought in Kenya Maasailand: pastoralists and farmers of the Loitokitok area, Kajiado District - Campbell, David (1978)
Keywords: openalex:import

English in Kenyan education - Campbell, David A.; Walsh, Patrick (Intercultural Education, 2009)
This paper intends not only to place English language teaching in Kenya within a specific historical context, but also to consider how it operates alongside the many other languages used in the day‐to‐day experiences of a secondary school community. Any consideration of the use of English in Kenya must take into account the legacy of language policies adopted by both colonial and independent administrations in the country. Use is made in this respect of the growing body of research and theory which focuses on language policy in post‐colonial and neo‐colonial settings. Therefore, an evaluation of the intentions and impact of these policies on attitudes towards language use is included in this paper.
Keywords: openalex:import

‘All have to live in me …’: a study of the use of English alongside other African languages in a Kenyan school - Campbell, David A.; Walsh, Patrick (Intercultural Education, 2010)
The purpose of this paper, which builds on an earlier paper published in this Journal (Vol. 20, No. 6), is to develop the discussion around how English has been taught, used and perceived in Kenya, using data gathered from a small second‐level English‐medium school in Kenya. The complex relationships between language and identity are at work in the everyday routines of both staff and pupils within such a context. The paper seeks to set out a clear methodology for gathering data which could help describe these relationships with more clarity while also subjecting the data to analysis informed by the growing body of research and theory that focuses on language policy in post‐colonial and neo‐colonial settings. Finally, these pieces of data are used as the basis of a further exploration of the implications for classroom practice in teaching English in this environment.
Keywords: openalex:import

Growth Faltering in Rural Gambian Infants Is Associated with Impaired Small Intestinal Barrier Function, Leading to Endotoxemia and Systemic Inflammation - Campbell, David I.; Elia, Marinos; Lunn, P. G. (The Journal of nutrition (Print), 2003)
Growth faltering of rural Gambian infants is associated with a chronic inflammatory enteropathy of the mucosa of the small intestine that may impair both digestive/absorptive and barrier functions. The aim of this study was to determine whether the enteropathy was associated with a compromised barrier function that allowed translocation of antigenic macromolecules from the gut lumen into the body, with subsequent systemic immunostimulation, resulting in growth retardation. Rural Gambian infants were studied longitudinally at regular intervals between 8 and 64 wk of age. On each study day, each child was medically examined, anthropometric measurements were made, a blood sample was taken and an intestinal permeability test performed. Evidence of chronic immunostimulation was provided by abnormally elevated white blood cell, lymphocyte and platelet counts, and frequently raised plasma concentration of C-reactive protein. Intestinal permeability was abnormal and associated with impaired growth (r = -0.41, P < 0.001). Plasma concentrations of endotoxin and immunoglobulin (Ig)G-endotoxin core antibody were also elevated and related to both growth (r = -0.30, P < 0.02; r = -0.64, P < 0.0001, respectively) and measures of mucosal enteropathy. Plasma IgG, IgA and IgM levels increased rapidly with age toward adult concentrations. Raised values were related to poor growth but also to measures of mucosal enteropathy and the endotoxin antibody titer. The interrelationships among these variables and growth suggested that they were all part of the same growth-retarding mechanism. These data are consistent with the hypothesis of translocation of immunogenic lumenal macromolecules across a compromised gut mucosa, leading to stimulation of systemic immune/inflammatory processes and subsequent growth impairment.
Keywords: openalex:import

Pluralistic modelling approaches to simulating climate-land change interactions in East Africa - Pijanowski, Bryan C.; Washington-Ottombre, Camille; Campbell, David; Olson, J.; Moore, Nathan; Alexandridis, Kostas (2007)
We summarize the use of several different modelling approaches we are employing to understand how climate change impacts changes in land use in East Africa. A role playing game model has been employed that helps to elucidate the behavioural drivers of land use change and how these factors are integrated with other biophysical (e.g. climate) and socioeconomic drivers. Outcomes from the game include a qualitative list and integrative understanding of these drivers over spatial and temporal scales and a series of decision maps produced by game participants. A second method includes the use of expert systems or knowledge acquisition approaches that attempt to synthesize expert opinion on how societies may adapt to changes in climate. Outcomes of these knowledge acquisition activities include expert maps and systems diagrams both of which are used to construct and validate models. These two qualitative approaches were used to construct three different sets of models: those that use multi-criteria evaluation techniques integrating a variety of spatial data layers using a geographic information system; a machine learning based model employing artificial neural networks that learn from patterns in data, and a behavioural model using Bayesian Belief Networks that simulates individual behaviour in the context of social interactions. We show how these diverse methods are used together to aid in our understanding of the drivers and impacts of climate change on land use systems in East Africa. In particular, we are interested in the impacts climate change might have on pastoralist, cropping, and urban systems over the next 10-50 years. These methods are being used along with process based models of regional climate change and crop production models to understand the coupling of climate and land systems in this geographically diverse area of the world. In our discussion we compare and contrast these very different, but complementary, modelling approaches to understand climate change at local to regional scales.
Keywords: openalex:import

Food production risks associated with land use change and climate change in East Africa - Moore, Nathan; Alagarswamy, G.; Pijanowski, B.C.; Thornton, P. E.; Olson, J.; Lofgren, Brent M.; Andresen, Jeff; Campbell, David (IOP Conference Series: Earth and Environmental Science, 2009)
Keywords: openalex:import